A Novel Anti-human DR5 Monoclonal Antibody with Tumoricidal Activity Induces Caspase-dependent and Caspase-independent Cell Death - Yabin Guo; Caifeng Chen; Yong Zheng; Jinchun Zhang; Xiaohui Tao; Shilian Liu; Dexian Zheng; Yanxin Liu (2005)
Like anti-Fas monoclonal antibodies, some monoclonal antibodies against tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptors have tumoricidal activity too. In this article we report a novel mouse anti-human DR5 monoclonal antibody, AD5–10, that induces apoptosis of various tumor cell lines in the absence of second cross-linking in vitro and showed strong tumoricidal activity in vivo. AD5–10 does not compete with TRAIL for binding to DR5 and synergizes with TRAIL to induce apoptosis of tumor cells. AD5–10 induces both caspase-dependent and caspase-independent cell death in Jurkat cells, whereas TRAIL induces only caspase-dependent cell death. We show for the first time that DR5 can mediate caspase-independent cell death, and DR5 can mediate distinct cell signals when interacting with different extracellular proteins. Studies on AD5–10 help us to understand more on the functions of DR5 and may provide new ideas for cancer immunotherapy. Like anti-Fas monoclonal antibodies, some monoclonal antibodies against tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptors have tumoricidal activity too. In this article we report a novel mouse anti-human DR5 monoclonal antibody, AD5–10, that induces apoptosis of various tumor cell lines in the absence of second cross-linking in vitro and showed strong tumoricidal activity in vivo. AD5–10 does not compete with TRAIL for binding to DR5 and synergizes with TRAIL to induce apoptosis of tumor cells. AD5–10 induces both caspase-dependent and caspase-independent cell death in Jurkat cells, whereas TRAIL induces only caspase-dependent cell death. We show for the first time that DR5 can mediate caspase-independent cell death, and DR5 can mediate distinct cell signals when interacting with different extracellular proteins. Studies on AD5–10 help us to understand more on the functions of DR5 and may provide new ideas for cancer immunotherapy. Tumor necrosis factor (TNF) 2The abbreviations used are: TNFtumor necrosis factorTRAILTNF-related apoptosis-inducing ligandsTRAILsoluble TRAILrsTRAILrecombinant soluble TRAILTRAIL-RTRAIL receptormAbmonoclonal antibodyDDdeath domainDRdeath receptorRIPreceptor-interacting proteinCasp-8-DNcaspase-8 dominant-negativePARPpoly(ADP-ribose) polymeraseJNKc-Jun N-terminal kinaseMAPKmitogen-activated protein kinaseELISAenzyme-linked immunosorbent assayZ-N-benzyloxycarbonyl-fmkfluoromethyl ketonePMAphorbol 12-myristate 13-acetateCHXcycloheximideMTS3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium.2The abbreviations used are: TNFtumor necrosis factorTRAILTNF-related apoptosis-inducing ligandsTRAILsoluble TRAILrsTRAILrecombinant soluble TRAILTRAIL-RTRAIL receptormAbmonoclonal antibodyDDdeath domainDRdeath receptorRIPreceptor-interacting proteinCasp-8-DNcaspase-8 dominant-negativePARPpoly(ADP-ribose) polymeraseJNKc-Jun N-terminal kinaseMAPKmitogen-activated protein kinaseELISAenzyme-linked immunosorbent assayZ-N-benzyloxycarbonyl-fmkfluoromethyl ketonePMAphorbol 12-myristate 13-acetateCHXcycloheximideMTS3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium.-related apoptosis-inducing ligand (TRAIL) is a member of the TNF superfamily with the ability to induce apoptosis in a wide variety of transformed cell lines of diverse origin (1Wiley S.R. Schooley K. Smolak P.J. Din W.S. Huang C.P. Nicholl J.K. Sutherland G.R. Smith T.D. Rauch C. Smith C.A. Goodwin R.G. Immunity. 1995; 3: 673-682Abstract Full Text PDF PubMed Scopus (2635) Google Scholar). At least five receptors for TRAIL have been identified so far. Two of them, DR4 (TRAIL-R1) and DR5 (TRAIL-R2/TRICK2) (2Pan G. O'Rourke K. Chinnaiyan A.M. Gentz R. Ebner R. Ni J. Dixit V.M. Science. 1997; 276: 111-113Crossref PubMed Scopus (1546) Google Scholar, 3Walczak H. Degli-Esposti M.A. Johnson R.S. Smolak P.J. Waugh J.Y. Boiani N. Timour M.S. Gerhart M.J. Schooley K.A. Smith C.A. Goodwin R.G. Rauch C.T. EMBO J. 1997; 16: 5386-5397Crossref PubMed Scopus (1013) Google Scholar, 4Chaudhary P.M. Eby M. Jasmin A. Bookwalter A. Murray J. Hood L. Immunity. 1997; 7: 821-830Abstract Full Text Full Text PDF PubMed Scopus (607) Google Scholar), are capable of transducing an apoptosis signal, whereas the other three, decoy receptor (DcR) 1 (TRAIL-R3) (5Degli-Esposti M.A. Smolak P.J. Walczak H. Waugh J. Huang C.P. DuBose R.F. Goodwin R.G. Smith C.A. J. Exp. Med. 1997; 186: 1165-1170Crossref PubMed Scopus (556) Google Scholar), DcR2 (TRAIL-R4) (6Degli-Esposti M.A. Dougall W.C. Smolak P.J. Waugh J.Y. Smith C.A. Goodwin R.G. Immunity. 1997; 7: 813-820Abstract Full Text Full Text PDF PubMed Scopus (742) Google Scholar), and osteoprotegerin (7Emery J.G. McDonnell P. Burke M.B. Deen K.C. Lyn S. Silverman C. Dul E. Appelbaum E.R. Eichman C. DiPrinzio R. Dodds R.A. James I.E. Rosenberg M. Lee J.C. Young P.R. J. Biol. Chem. 1998; 273: 14363-14367Abstract Full Text Full Text PDF PubMed Scopus (1049) Google Scholar), serve as decoy receptors to block TRAIL-mediated apoptosis. DR4 and DR5 share a common intracellular domain, called the death domain (DD), which is indispensable for initiation of the intracellular signaling cascade leading to cell death. The death domain motif is also found in the cytoplasmic adaptor proteins, such as Fas-associated protein with death domain (FADD) (8Chinnaiyan A.M. O'Rourke K. Tewari M. Dixit V.M. Cell. 1995; 81: 505-512Abstract Full Text PDF PubMed Scopus (2149) Google Scholar), TNF-R1-associated death domain protein (TRADD) (9Hsu H. Xiong J. Goeddel D.V. Cell. 1995; 81: 495-504Abstract Full Text PDF PubMed Scopus (1734) Google Scholar), and receptor-interacting protein (RIP) (10Lin Y. Devin A. Cook A. Keane M.M. Kelliher M. Lipkowitz S. Liu Z.G. Mol. Cell Biol. 2000; 20: 6638-6645Crossref PubMed Scopus (189) Google Scholar), etc. These adaptor proteins are essential for the intracellular signals mediated by DR4 and DR5 (11Schneider P. Thome M. Burns K. Bodmer J.L. Hofmann K. Kataoka T. Holler N. Tschopp J. Immunity. 1997; 7: 831-836Abstract Full Text Full Text PDF PubMed Scopus (590) Google Scholar). TRAIL triggers multiple cell signals, including the activation of apoptotic caspase cascade, c-Jun N-terminal kinase (JNK), p38 mitogen-activated protein kinase (MAPK) and NF-κB (11Schneider P. Thome M. Burns K. Bodmer J.L. Hofmann K. Kataoka T. Holler N. Tschopp J. Immunity. 1997; 7: 831-836Abstract Full Text Full Text PDF PubMed Scopus (590) Google Scholar, 12Muhlenbeck F. Haas E. Schwenzer R. Schubert G. Grell M. Smith C. Scheurich P. Wajant H. J. Biol. Chem. 1998; 273: 33091-33098Abstract Full Text Full Text PDF PubMed Scopus (125) Google Scholar, 13Jeremias I. Debatin K.M. Eur. Cytokine Netw. 1998; 9: 687-688PubMed Google Scholar).In contrast to TNFs and Fas ligand, TRAIL has been known to induce apoptosis in a variety of tumor cells and some virally infected cells but not in most normal cells. The potential and safety of soluble TRAIL (sTRAIL) as an anticancer therapeutic agent have been demonstrated in mice and non-human primates (14Walczak H. Miller R.E. Ariail K. Gliniak B. Griffith T.S. Kubin M. Chin W. Jones J. Woodward A. Le T. Smith C. Smolak P. Goodwin R.G. Rauch C.T. Schuh J.C. Lynch D.H. Nat. Med. 1999; 5: 157-163Crossref PubMed Scopus (2212) Google Scholar, 15Ashkenazi A. Pai R.C. Fong S. Leung S. Lawrence D.A. Marsters S.A. Blackie C. Chang L. McMurtrey A.E. Hebert A. DeForge L. Koumenis I.L. Lewis D. Harris L. Bussiere J. Koeppen H. Shahrokh Z. Schwall R.H. J. Clin. Investig. 1999; 104: 155-162Crossref PubMed Scopus (1985) Google Scholar). However, increasing experimental evidence on TRAIL-inducing apoptosis of normal cells (especially hepatocytes) were reported in recent studies (16Jo M. Kim T.H. Seol D.W. Esplen J.E. Dorko K. Billiar T.R. Strom S.C. Nat. Med. 2000; 6: 564-567Crossref PubMed Scopus (764) Google Scholar, 17Nitsch R. Bechmann I. Deisz R.A. Haas D. Lehmann T.N. Wendling U. Zipp F. Lancet. 2000; 356: 827-828Abstract Full Text Full Text PDF PubMed Scopus (274) Google Scholar), arguing against the potential usefulness and safety of soluble TRAIL in cancer therapy. Meanwhile, there were also reports demonstrating that recombinant TRAIL without exogenous sequence tags was nontoxic to human hepatocytes both in vitro (18Lawrence D. Shahrokh Z. Marsters S. Achilles K. Shih D. Mounho B. Hillan K. Totpal K. DeForge L. Schow P. Hooley J. Sherwood S. Pai R. Leung S. Khan L. Gliniak B. Bussiere J. Smith C.A. Strom S.S. Kelley S. Fox J.A. Thomas D. Ashkenazi A. Nat. Med. 2001; 7: 383-385Crossref PubMed Scopus (633) Google Scholar, 19Shi J. Liu Y. Li X. Zheng D. Chin. J. Bioeng. 2003; 23: 46-49Google Scholar) and in chimeric mice (20Hao C. Song J.H. Hsi B. Lewis J. Song D.K. Petruk K.C. Tyrrell D.L. Kneteman N.M. Cancer Res. 2004; 64: 8502-8506Crossref PubMed Scopus (128) Google Scholar). In addition to sTRAIL, monoclonal antibodies (mAbs) against TRAIL receptors with tumoricidal activity are also potential candidates for cancer therapy. There are a number of agonistic mAbs against human DR4 or DR5 reported in previous studies (21Griffith T.S. Rauch C.T. Smolak P.J. Waugh J.Y. Boiani N. Lynch D.H. Smith C.A. Goodwin R.G. Kubin M.Z. J. Immunol. 1999; 162: 2597-2605PubMed Google Scholar, 22Chuntharapai A. Dodge K. Grimmer K. Schroeder K. Marsters S.A. Koeppen H. Ashkenazi A. Kim K.J. J. Immunol. 2001; 166: 4891-4898Crossref PubMed Scopus (184) Google Scholar, 23Ichikawa K. Liu W. Zhao L. Wang Z. Liu D. Ohtsuka T. Zhang H. Mountz J.D. Koopman W.J. Kimberly R.P. Zhou T. Nat. Med. 2001; 7: 954-960Crossref PubMed Scopus (497) Google Scholar), most of which need cross-linkers to ensure effective killing of tumor cells (21Griffith T.S. Rauch C.T. Smolak P.J. Waugh J.Y. Boiani N. Lynch D.H. Smith C.A. Goodwin R.G. Kubin M.Z. J. Immunol. 1999; 162: 2597-2605PubMed Google Scholar, 22Chuntharapai A. Dodge K. Grimmer K. Schroeder K. Marsters S.A. Koeppen H. Ashkenazi A. Kim K.J. J. Immunol. 2001; 166: 4891-4898Crossref PubMed Scopus (184) Google Scholar). In 2001, Ichikawa et al. (23Ichikawa K. Liu W. Zhao L. Wang Z. Liu D. Ohtsuka T. Zhang H. Mountz J.D. Koopman W.J. Kimberly R.P. Zhou T. Nat. Med. 2001; 7: 954-960Crossref PubMed Scopus (497) Google Scholar) reported a mouse anti-DR5 mAb, TRA-8, that showed strong tumoricidal activity in the absence of cross-linking and had no hepatocyte toxicity. TRA-8 competes with TRAIL for binding to DR5 and almost entirely mimics the apoptosis-inducing mechanism of TRAIL. The authors believed that DR5 was not sufficient to trigger apoptosis in normal hepatocytes (23Ichikawa K. Liu W. Zhao L. Wang Z. Liu D. Ohtsuka T. Zhang H. Mountz J.D. Koopman W.J. Kimberly R.P. Zhou T. Nat. Med. 2001; 7: 954-960Crossref PubMed Scopus (497) Google Scholar). However, a recent study showed that at least some anti-DR5 and anti-DR4 mAbs did induce human hepatocytes apoptosis (24Mori E. Thomas M. Motoki K. Nakazawa K. Tahara T. Tomizuka K. Ishida I. Kataoka S. Cell Death Differ. 2004; 11: 203-207Crossref PubMed Scopus (73) Google Scholar). Therefore, we cannot draw a definite conclusion on the hepatocyte toxicity of soluble TRAIL or mAbs against TRAIL receptors now. Studies on the mechanism of anti-DR5 mAbs will help us to understand the complicated signal pathways mediated by DR5.In this article, we report studies on AD5–10, a novel monoclonal antibody against human DR5. AD5–10 induces apoptosis in various tumor cell lines in the absence of second cross-linking in vitro and exhibits a strong tumoricidal activity in vivo. AD5–10 does not induce cell death of human normal hepatocytes and primary peripheral blood lymphocytes, and the injection with high doses of AD5–10 in mice causes no toxic reaction in liver, spleen, and kidney. Unlike TRA-8, AD5–10 does not compete with TRAIL for binding to DR5, and there is a synergistic effect between TRAIL and AD5–10 on their tumoricidal activity. Downstream cell signals induced by AD5–10 and TRAIL were also compared. Both TRAIL and AD5–10 activate caspase cascade and induce a classical apoptosis in Jurkat cells. Interestingly, AD5–10 kills Jurkat cells in the presence of Z-VAD, whereas TRAIL does not, indicating a caspase-independent cell death promoted by AD5–10. Furthermore, we show that RIP is essential for this caspase-independent cell death. Z-VAD inhibits the activation of JNK/p38 by TRAIL but not AD5–10. Both TRAIL and AD5–10 are capable of activating of NF-κB, but there are differences between the regulation of NF-κB activity by TRAIL and that by AD5–10 in certain cell lines. These findings show that DR5 can mediate distinct cell signals when interacting with different extracellular proteins. The differences in the cell signals induced by AD5–10 and TRAIL are undoubtedly significant for further studies. Illustration of the mechanisms may lead to the development of new strategies for cancer immunotherapy.MATERIALS AND METHODSReagents—Z-VAD-fmk (a pan-caspase inhibitor) was purchased from R&D Systems, Inc. (Minneapolis, MN). Phorbol 12-myristate 13-acetate (PMA) was purchased from Promega Co. (Madison, WI). pGL2 plasmid, the luciferase reporter vector, was from Promega. Caspase-8 dominant-negative plasmid was kindly provided by Dr. Shimin Hu (University of Pennsylvania). Recombinant soluble TRAIL (rsTRAIL, amino acids 95–281, nontagged) was prepared as previously described by Shi et al. (19Shi J. Liu Y. Li X. Zheng D. Chin. J. Bioeng. 2003; 23: 46-49Google Scholar). His-DR4 (histidine-tagged extracellular domain of human DR4; amino acids 110–240), His-DR5 (histidine-tagged extracellular domain of human DR5a; amino acids 52–183), and His-DR5-ΔL2 (histidine-tagged extracellular domain of humanDR5a; amino acids 52–183 with a deletion of amino acids 94–113) were expressed in Escherichia coli and purified using nickel nitrilotriacetic acid His-Bind resin (Novagen, Inc., Milwaukee, WI). Anti-caspase-8 and anti-caspase-9 antibodies were purchased from Calbiochem. Anti-TRAIL, anti-caspase-3, anti-poly(ADP-ribose) polymerase (PARP), anti-actin, anti-phospho-JNK, anti-JNK, anti-p38, anti-phospho-IκB, and anti-IκB antibodies were purchased from Santa Cruz Biotechnology, Inc. (Santa Cruz, CA). Anti-phospho-p38 antibody was purchased from Cell Signaling Technology, Inc. (Beverly, MA). Horseradish peroxidase-linked anti-mouse IgG, anti-rabbit IgG and anti-goat IgG were purchased from ZhongShan Co. (Beijing, China).ELISA—ELISA plates (Costar) were coated with 5 μg/ml His-DR4, His-DR5, or His-DR5-ΔL2 and blocked with 5% nonfat dry milk. Plates were then incubated with 100 μl/well of mAbs (or hybridoma culture supernatants) at the required dilutions. The bound mAbs were detected with 100 μl/well of horseradish peroxidase-goat anti-mouse IgG. For the binding of rsTRAIL, plates were incubated with 100 μl/well of rsTRAIL. After washing, 100 μl/well of rabbit anti-TRAIL antibody was added to wells. The specific binding was then detected with horseradish peroxidase-goat anti-rabbit IgG. The absorbency at 492 nm was measured on a microtiter reader (Thermo Labsystems). The results were analyzed using GraphPad Prism (GraphPad software, San Diego, CA).Cell Culture and Cell Viability Assay—SMMC-7721 cells and U251 cells were purchased from the Committee on Type Culture Collection of Chinese Academy of Sciences (Shanghai, China). Other tumor cell lines were purchased from American Type Culture Collection (ATCC, Manassas, VA). HL-60-R cells were derived from HL-60 cells (ATCC). RIP-deficient Jurkat cells were kindly provided by Dr. Brian Seed (Department of Molecular Biology, Massachusetts General Hospital, Boston, MA). Normal human hepatocytes were provided by the Cancer Institute and Hospital, Chinese Academy of Medical Sciences (Beijing, China). Normal human primary peripheral blood lymphocytes cells were isolated from peripheral blood of healthy volunteers. Tumor cell lines and primary cells were cultured in RPMI 1640 medium (Invitrogen) supplemented with 10% heat-inactivated fetal calf serum (Hyclone, Logan, UT), penicillin (100 units/ml), and streptomycin (100 μg/ml) at 37 °C in a humidified atmosphere of 5% CO2. Hybridomas were cultured in Dulbecco's modified Eagle's medium (Invitrogen) supplemented with 10% heat-inactivated fetal calf serum and antibiotics as described above. Cell viability was determined using CellTiter 96 AQueous nonradioactive cell proliferation assay (MTS) according to the manufacturer's instructions (Promega). Z-VAD-fmk or PMA was added 30 min before the addition of stimulants.Generation of AD5–10—4-Week-old female BALB/c mice were immunized 4 times with 50 μg of DR5 extracellular domain protein at 2-week intervals. Three days after the final boost, lymphocytes from spleen were fused with SP2/0 myeloma cells (ATCC), and positive hybridomas were screened against DR5 and His-DR5 recombinant protein using ELISA. The selected mAbs were further tested for their tumoricidal activity.Annexin-V and Propidium Iodide Staining—Cells after the indicated treatment were stained using the annexin-V kit according to the manufacturer's instructions (BioSea Biotech Co., Beijing, China). Briefly, cells were washed once with phosphate-buffered saline and stained in 200 μl of binding buffer containing annexin-V-fluorescein isothiocyanate for 30 min on ice. Propidium iodide was then added into the buffer. 5 min later 300 μl of binding buffer was added. The samples were analyzed with a flow cytometer (FACScan, BD Biosciences). 10,000 cells were counted per sample.Western Blot Analysis—After the required treatments, cells (2–3 × 106) were washed once with phosphate-buffered saline and lysed in the sample buffer (80–120 μl) for SDS-PAGE and immediately boiled for 5 min. Each sample was subjected to 8, 10, or 12% SDS-PAGE, and the proteins separated in the gel were subsequently electrotransferred onto a polyvinylidene difluoride membrane (Amersham Biosciences). The membrane was blocked with 5% nonfat dry milk in TBS-T (20 mmTris-HCl (pH 7.4), 8 g/liter NaCl, and 0.1% Tween 20) for 1–2 h at room temperature. The membrane was then incubated with the indicated primary antibodies in TBS-T containing 5% nonfat dry milk at 4 °C overnight. The membrane was washed 3 times with TBS-T and probed with horseradish peroxidase-conjugated secondary antibodies at room temperature for 1.5–2 h. After washing four times with TBS-T, the protein was visualized using the ECL Plus Western blotting detection system according to the manufacturer's instructions (Amersham Biosciences).Analysis of Tumoricidal Activity in Vivo—6–8-Week-old female BALB/c nude mice were inoculated subcutaneously with SMMC-7721 cells (2 × 106). Three weeks later, after the indicated treatment, the mice were sacrificed, and the growth of tumor cells was determined by the weight of the tumor mass. 6–8-Week-old female BALB/c nude mice were inoculated subcutaneously with A549 cells (2 × 106). One month later, after the indicated treatment, the mice were sacrificed, and the growth of tumor cells was determined by the weight of the tumor mass. Construction of Casp-8-DN Jurkat Cells—Jurkat cells were transfected with Casp-8-DN plasmid using the cell line Nucleofector kit V (Amaxa Biosystem) according to the manufacturer's instructions and screened with G418 (Alexis Biochemicals, San Diego, CA).Electron Microscopy—After the indicated treatment cells were fixed by dropwise addition of glutaraldehyde and analyzed according to standard procedures.DNA Fragmentation Assay—After the required treatments, 2 × 106 cells were collected and washed once with phosphate-buffered saline and lysed in 100 μl of buffer containing 10 mm Tris-HCl (pH 7.4), 10 mm EDTA, and 0.5% Triton X-100. Lysates were centrifuged at 14,000 × g for 5 min at 4 °C, and supernatants were then subjected to digestion with ribonuclease A (0.2 mg/ml) for 1 h at 37 °C followed by incubation with proteinase K (0.2 mg/ml) for 1 h at 37°C.DNA in the sample was precipitated by centrifugation at 14,000 × g for 15 min at 4 °C after treatment with 50% isopropyl alcohol and 0.5 m NaCl overnight at –20 °C. DNA was resuspended in 30 μl of Tris-EDTA buffer and analyzed by electrophoresis on a 2% agarose gel in the presence of 0.2 μg/ml ethidium bromide.NF-κB Activation Assay—The NF-κB reporter plasmid was constructed as previously described (25Wang M. Liu Y. Liu S. Zheng D. Oncol. Rep. 2004; 12: 193-199PubMed Google Scholar). The two primers, p1 (5′-GCGAGCTCGGGACTTTCCGGGACTTTCCGGGACT-3′, containing SacI cut site (underlined)) and p2, 5′-CCGCTCGAGGGAAAGTCCCGGAAGTCCCGGAAAG-3′, containing XhoI cut site (underlined)) were synthesized by BioAsia Co. (Shanghai, China). The overlapped sequences in the primers are indicated in italics. The primers were annealed to each other and amplified using PCR. The product corresponding to the three repeats of NF-κB DNA binding sequence was then cut with SacI and XhoI restriction endonucleases and inserted into the polyclonal sites of pGL2 plasmid (Promega). The recombinant plasmid was designated as pGL2-NF-κB. Cells were transfected with pGL2-NF-κB using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions. Equal count of transfected cells were treated, and luciferase activity in the cells was then determined using luciferase reporter assay system (Promega).Statistical Analysis—Results were expressed as mean values ± S.D.), and a Student's t test was used for evaluating statistical significance. p values were considered to be statistically significant when less than 0.05.RESULTSAD5–10 Binds to DR5 Specifically and Does Not Compete with TRAIL—Human DR5 has two isoforms, designated as DR5a and DR5b, which is a result of pre-mRNA alternative splicing. DR5b has an insertion of 29 amino acids in the extracellular domain compared with DR5a (26Screaton G.R. Mongkolsapaya J. Xu X.N. Cowper A.E. McMichael A.J. Bell J.I. Curr. Biol. 1997; 7: 693-696Abstract Full Text Full Text PDF PubMed Scopus (285) Google Scholar). AD5–10 (IgG3-κ) was generated by immunizing BALB/c mice with a recombinant protein containing simply the extracellular domain of DR5a (amino acids 52–183), which was expressed in E. coli and without any exogenous sequence tags. In previous studies on anti-TRAIL receptor mAbs, DR4-Fc and DR5-Fc fusion proteins were usually used as antigens for immunizing animals (21Griffith T.S. Rauch C.T. Smolak P.J. Waugh J.Y. Boiani N. Lynch D.H. Smith C.A. Goodwin R.G. Kubin M.Z. J. Immunol. 1999; 162: 2597-2605PubMed Google Scholar, 22Chuntharapai A. Dodge K. Grimmer K. Schroeder K. Marsters S.A. Koeppen H. Ashkenazi A. Kim K.J. J. Immunol. 2001; 166: 4891-4898Crossref PubMed Scopus (184) Google Scholar, 23Ichikawa K. Liu W. Zhao L. Wang Z. Liu D. Ohtsuka T. Zhang H. Mountz J.D. Koopman W.J. Kimberly R.P. Zhou T. Nat. Med. 2001; 7: 954-960Crossref PubMed Scopus (497) Google Scholar). We showed that the bacterially expressed DR4 and DR5 extracellular regions bound to their natural ligand, TRAIL, specifically (Fig. 1A), indicating that they are suitable for immunizing animals. There are two different TRAIL-binding sites on both DR4 and DR5 molecules (Kdhigh = 5–10 nm; Kdlow = 800–5000 nm) as previously described (5Degli-Esposti M.A. Smolak P.J. Walczak H. Waugh J. Huang C.P. DuBose R.F. Goodwin R.G. Smith C.A. J. Exp. Med. 1997; 186: 1165-1170Crossref PubMed Scopus (556) Google Scholar, 6Degli-Esposti M.A. Dougall W.C. Smolak P.J. Waugh J.Y. Smith C.A. Goodwin R.G. Immunity. 1997; 7: 813-820Abstract Full Text Full Text PDF PubMed Scopus (742) Google Scholar). In contrast, AD5–10 bound to DR5 via one binding site (Kd = 0.30 nm) and did not react with DR4 and Fas (Fig. 1B). Notably, competitive ELISA showed that there was no competition between AD5–10 and TRAIL for binding to DR5 (Fig. 1, C and D). There are 7 disulfide bonds on the extracellular domain of DR5. The loop (amino acids 94–113) formed by the second disulfide bond (from the N terminus) has been demonstrated essential for DR5 to interact with TRAIL (27Hymowitz S.G. Christinger H.W. Fuh G. Ultsch M. O'Connell M. Kelley R.F. Ashkenazi A. de Vos A.M. Mol. Cell. 1999; 4: 563-571Abstract Full Text Full Text PDF PubMed Scopus (367) Google Scholar). We expressed amino acids 94–113-deleted DR5 extracellular domain, designated as DR5-ΔL2 in E. coli, for the binding assay. The result showed that TRAIL did not bind to DR5-ΔL2, whereas AD5–10 bound to DR5-ΔL2 specifically (Fig. 1E), indicating that AD5–10 and TRAIL bound to different sites on DR5, raising the possibility that AD5–10 and TRAIL may trigger different downstream cell signals.AD5–10 Induces Apoptosis in Multiple Tumor Cell Lines in Vitro and Is Nontoxic to Human Normal Cells—Whether AD5–10 can kill tumor cells like TRAIL is what we are most interested in. Our results showed that AD5–10 and rsTRAIL strongly induced cell death in Jurkat cells. When treated with 100 ng/ml AD5–10, about 40% of Jurkat cells presented annexin-V positive after 1 h, and about 80% cells presented annexin-V positive after 2 h (Fig. 2, A and B). Cell viability was also tested using MTS kit (Promega). The IC50 (inhibitory concentration 50%) of Jurkat cells treated with AD5–10 for 8 h was less than 10 ng/ml (Fig. 2C). Furthermore, various tumor cell lines, SMMC-7721 (human hepatocellular carcinoma cells), HeLa cells, MDA-MB-231 (human breast adenocarcinoma cells), U251 (human glioma cells), and HCT-116 (colorectal carcinoma cells) were killed by AD5–10 as well as rsTRAIL in a concentration-dependent manner (Fig. 2, D and E). We noticed that Jurkat cells are more susceptible to AD5–10 than to rsTRAIL (Fig. 2, A–C), whereas apoptosis in HeLa cells were more easily induced by rsTRAIL (Fig. 2, D and E), which suggested that different mechanisms may be utilized by the two proteins. Nevertheless, these data demonstrated that both AD5–10 and rsTRAIL could efficiently induce cell death in various tumor cell lines in the absence of second cross-linking in vitro.FIGURE 2AD5–10 and rsTRAIL induced tumor cells but not normal cell apoptosis in vitro. A and B, annexin-V and propidium iodide (PI) staining flow cytometry. Jurkat cells were treated with 100 ng/ml rsTRAIL or AD5–10 for 2 h (A) or 1 or 2 h (B). FITC, fluorescein isothiocyanate. C, Jurkat cells were treated with the indicated concentrations of rsTRAIL or AD5–10 for 8 h. Cell viability was determined by an MTS assay. D and E, tumor cell lines were treated with the indicated concentrations of rsTRAIL (D) or AD5–10 (E) for 24 h. F and G, human normal hepatocytes were treated with the indicated concentrations of rsTRAIL (F) or AD5–10 (G) in the presence or absence of 1 μg/ml CHX for 24 h. Cell viability was determined by an MTS assay. Results shown are the average of triplicate measurements and a representative of at least three independent experiments.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Some versions of soluble TRAIL and some mAbs against TRAIL receptors were reported toxic to human normal hepatocytes, whereas others were demonstrated nontoxic. To test if AD5–10 has normal cell toxicity, we treated human hepatocytes with various concentrations of rsTRAIL or AD5–10 for 24 h. No decrease of cell viability was detected, as determined by MTS assay (Fig. 2, F and G). We also tested if cycloheximide (CHX), a potent apoptosis enhancer, could sensitize hepatocytes to TRAIL or AD5–10-induced cell death. A 24-h co-incubation with CHX and 10 ng/ml rsTRAIL caused a 40% decrease of hepatocyte viability. In contrast, no decrease of cell viability was detected in cultures exposed to both CHX and various concentrations of AD5–10 (Fig. 2, F and G). Our results showed that both rsTRAIL and AD5–10 were nontoxic to human hepatocytes and suggested that AD5–10 was relatively safer to human hepatocytes than TRAIL. In addition, rsTRAIL, AD5–10, or the combination of the two agents was also nontoxic to human primary peripheral blood lymphocytes (data not shown).Tumoricidal Activity of AD5–10 in Vivo—The tumoricidal activity of AD5–10 in vivo was tested using two tumor cell lines. BALB/c nude mice were inoculated subcutaneously with SMMC-7721, a human hepatocellular carcinoma cell line, or A549, a human lung carcinoma cell line. Both rsTRAIL and AD5–10 inhibited the SMMC-7721, forming solid tumors in early treatment or reduced tumor weight in late treatment significantly. The tumor weights were reduced 4–5-fold as compared with control treatments (Fig. 3 A and B). Tumor formation was completely invisible in 4 animals with AD5–10 early treatment (n = 10), and the tumors of 5 animals with AD5–10 late treatment completely disappeared (n = 10). An example from AD5–10-treated mice was shown along with one from control mice in Fig. 3C. Similarly, AD5–10 inhibited the growth of A549 cells in BALB/c nude mice (Fig. 3D). These results indicate that AD5–10 is a potent inhibitor of in vivo tumor cell growth. Injection with extremely high doses of rsTRAIL and AD5–10 (10-fold of the dose used in anti-tumor treatment experiments) to BALB/c mice caused no toxic reaction in liver, spleen, and kidney (data not shown).FIGURE 3Tumoricidal activity of AD5–10 in vivo. A and B, BALB/c nude mice were inoculated with SMMC-7721 cells and then injected with 3 doses of 100 μg of rsTRAIL, 3 doses of 100 μg of AD5–10, or a single dose of 1.2 mg CTX on the 2nd day (A) or the 8th day (B). Tumor growth was determined by weight. C, control mice (left) and mice with AD5–10 late treatment. D, BALB/c nude mice were inoculated with A549 cells and injected with a single dose or 3 doses of 100 μg of AD5–10 or a single dose of 0.8 mg of CTX on the 2nd day. Tumor growth was determined by weight.View Large Image